Pengaruh Pertumbuhan Penjualan, Pertumbuhan Perusahaan, Ukuran Perusahaan, dan Inflasi Terhadap Nilai Perusahaan - Mutifa, Mutia Rizky Nurul; Prasetio, Januar Eko (Equity: Jurnal Akuntansi, 2024)
The aim of this research is to empirically examine and determine the influence of inflation, company size, company growth, and sales growth on the firm value of property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2017 – 2022. The population in this study consists of 45 companies, with a sample size of 32 companies selected using purposive sampling techniques. The data used are secondary data, specifically financial reports obtained from both the official IDX website and the companies themselves. The data analysis technique employed is multiple linear regression analysis. The research results indicate that inflation and sales growth do not affect the firm value, while company growth and company size have a significant impact on the firm value.